An Analysis of Bank Efficiency in the Middle East and North Africa (International Journal of Banking and Finance, 2012)
This paper reports institutional factor effects on bank efficiency in Middle Eastern and North African countries during a recent 14 years. The methods used are: Stochastic Frontier Analyses and second-stage Tobit regression to investigate the impact of institutional-cum-financial as well as bank-specific variables on efficiency. Overall, the analysis shows that banks could save 20 percent of their total costs if they were operating efficiently. Factors that affect production efficiency are: macroeconomic stability, financial development, the degree of market competition, legal rights and contract laws, better governance and political stability. Differences in technology seem to be crucial in explaining efficiency differences. Our findings point to the importance of policies that aim to build stronger institutions, promote more competition, and improve governance. Policies should be aimed at giving banks incentives to improve their capitalization and liquidity. Improvements in the legal system and in the regulatory and supervisory bodies would also help to reduce inefficiency, areas of immediate concerns for this vast region. Finally, increased investments and upgrading of the stock markets in the region would help banks improve their performance through market-based investor actions.